FGF2 disruption enhances thermogenesis in brown and beige fat to protect against adiposity and hepatic steatosis - Haifang Li; Xinzhi Zhang; Cheng Huang; Huan Liu; Qiang Zhang; Qianying Sun; Yanxin Jia; Shuang Liu; Mei Dong; Mengjie Hou; Yiming Liu; Hai Lin (Elsevier, 2021)
Objective: Fibroblast growth factor 2 (FGF2) has been reported to play divergent roles in white adipogenic differentiation, however, whether it regulates thermogenesis of fat tissues remains largely unknown. We therefore aimed to investigate the effect of FGF2 on fat thermogenesis and elucidate the underlying mechanisms. Methods: FGF2-KO and wild-type (WT) mice were fed with chow diet and high-fat diet (HFD) for 14 weeks. The brown and white fat mass, thermogenic capability, respiratory exchange ratio, and hepatic fat deposition were determined. In vitro experiments were conducted to compare the thermogenic ability of FGF2-KO- with WT-derived brown and white adipocytes. Exogenous FGF2 was supplemented to in vitro-cultured WT brown and ISO-induced beige adipocytes. The FGFR inhibitor, PPARγ agonist, and PGC-1α expression lentivirus were used with the aid of technologies including Co-IP, ChIP, and luciferase reporter assay to elucidate the mechanisms underlying the FGF2 regulation of thermogenesis. Results: FGF2 gene disruption results in increased thermogenic capability in both brown and beige fat, supporting by increased UCP1 expression, enhanced respiratory exchange ratio, and elevated thermogenic potential in response to cold exposure. Thus, the deletion of FGF2 protects mice from high fat-induced adiposity and hepatic steatosis. Mechanistically, in vitro investigations indicated FGF2 acts in autocrine/paracrine fashions. Exogenous FGF2 supplementation inhibits both PGC-1α and PPARγ expression, leading to suppression of UCP1 expression in brown and beige adipocytes. Conclusions: These findings demonstrate that FGF2 is a novel thermogenic regulator, suggesting a viable potential strategy for using FGF2-selective inhibitors in combat adiposity and associated hepatic steatosis.